2019
DOI: 10.1001/jamapediatrics.2019.0624
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Stability of the Early Autism Spectrum Disorder Phenotype in the General Population Starting at 12 Months

Abstract: This study examines the diagnostic stability of autism spectrum disorder in a large cohort of toddlers starting at 12 months of age and compares this stability with that of toddlers with other disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
175
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(201 citation statements)
references
References 45 publications
2
175
0
5
Order By: Relevance
“…Autism spectrum disorder (ASD) is a neurodevelopmental disorder with an increasing global prevalence ranging from 42.6/10,000 in China to 1/58 in the United States 1,2 . ASD can be reliably diagnosed at 24 months or even as early as 18 months of age 3 , and is a life-long condition. Although the molecular and neural mechanisms underlying ASD remain largely unknown, a previous study suggested that ASD may result from alteration in brain development during early life, such as the excitatory-inhibitory (E-I) imbalance in the autistic brain can affect the sensory, memory and emotional systems 4 , indicating the necessity of early intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a neurodevelopmental disorder with an increasing global prevalence ranging from 42.6/10,000 in China to 1/58 in the United States 1,2 . ASD can be reliably diagnosed at 24 months or even as early as 18 months of age 3 , and is a life-long condition. Although the molecular and neural mechanisms underlying ASD remain largely unknown, a previous study suggested that ASD may result from alteration in brain development during early life, such as the excitatory-inhibitory (E-I) imbalance in the autistic brain can affect the sensory, memory and emotional systems 4 , indicating the necessity of early intervention.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the spatiotemporal activity of the DE-ASD network during brain development, we measured the magnitude of gene co-expression within the DE-ASD network at different neurodevelopmental time windows across brain regions. We found that the highest levels of co-expression of the DE-ASD network temporally coincided with peak neural proliferation in brain development (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) post conception weeks 3,8 ), after which co-expression activity gradually decreased ( Fig. 2c; Fig.…”
Section: The Leukocyte-based Gene Network Captures Transcriptional Prmentioning
confidence: 88%
“…The prevalence of ASD has steadily risen to the current rate of 1 in 54 children in the U.S. (Maenner et al, 2020). In the past decade, the age for a reliable diagnosis of ASD has decreased to as early as 14-months with the recommended age for early diagnosis at 18-months (Hyman, Levy, & Myers, 2020;Pierce et al, 2019). Early diagnosis has led to an increased demand for developmental and behavioral early intervention.…”
Section: Introductionmentioning
confidence: 99%